Mountain treasures - Barker, Jane Valentine, 1930-; Downing, Sybil; Diggs, Dian; Wilson, Robert F., (Robert Franklin), 1937- (Boulder, Colo. : Pruett Pub. Co., 1978)
Four stories describe life in Colorado's mountain mining camps of Leadville, Caribou, Ouray, and Cripple Creek in the late 1800's.
Bibliography: p. 44.
Keywords: Silver mines and mining -- Colorado -- Fiction; Mountain life -- Colorado -- Fiction; Colorado -- History -- Fiction; Short stories